Endoscopic Recognition and Management Strategies for Malignant Colorectal Polyps: Recommendations of the US Multi-Society Task Force on Colorectal Cancer - Shaukat, Aasma; Kaltenbach, Tonya; Dominitz, Jason A.; Robertson, Douglas J.; Anderson, Joseph C.; Cruise, Michael; Burke, Carol A.; Gupta, Samir; Lieberman, David; Syngal, Sapna; Rex, Douglas K. (The American journal of gastroenterology, 2020)
Specifically, we will discuss 6 key questions that address the following 3 tasks: endoscopic recognition of colorectal polyps with deep submucosal invasion that should be referred directly to surgery; optimal endoscopic resection techniques and specimen handling when an increased risk of superficial submucosally invasive polyp is identified; and weighing the risks and benefits of surgery when an endoscopically removed polyp is found to have submucosal invasion. Grading of Evidence The US Multi-Society Task Force on Colorectal Cancer (USMSTF) consists of gastroenterologists with expertise in colorectal neoplasia (ie, CRC and precursor lesions, such as polyps). According to this classification, malignant polyps would fall under category 5.2 (submucosal carcinoma and beyond).Table 2. [...]the use of terms such as carcinoma or cancer in describing lesions confined to the mucosa may cause undue alarm to endoscopists, surgeons, patients, or primary care providers, and can lead to unnecessary surgery.